Respuesta :

Answer:

The correct answer is -4.

Step-by-step explanation:

have a good day yall

Evaluating the function, f(x) = –2x² – 3x + 5 for x = -3, we would have: f(-3) = -4. (option B).

How do you Evaluate a Function?

To evaluate a function, plug in the given value of the input (x) and simplify.

Thus:

f(x) = –2x² – 3x + 5

Substitute x = -3 into the function

f(-3) = –2(-3)² – 3(-3) + 5

f(-3) = -2(9) + 9 + 5

f(-3) = -4

Therefore, evaluating the function, f(x) = –2x² – 3x + 5 for x = -3, we would have: f(-3) = -4. (option B).

Learn more about evaluation of function on:

https://brainly.com/question/17385640